STUDENT INTEREST IN CONTINUING STUDIES INTO HIGHER EDUCATION INFLUENCED BY SEVERAL FACTORS: FAMILY ECONOMIC STATUS, TYPE OF SCHOOL AND SCHOOL STATUS - Nurandi Jopa; Gatot Sugeng Purwono; Hary Sulaksono (STIE Mandala Jember, 2018)
This research aims to identify and analyze: 1) The influence of economic status of family, type of school and school status simultaneously against student interest in continuing their studies to university; 2) Effect of family economic status partially on student interest in continuing study on higher education; 3) The influence of type of school partially on student interest in continuing study on higher education; 4) Effect of school status partially on student interest in continuing study on higher education; and 5) Which variable is more dominant in influencing student interest in continuing study to college on students in Secondary School level in the Kedaleman Village, Rogojampi Sub-district, Banyuwangi District. The sampling technique used incidental technique and Snowball sampling as many as 50 students. The data collection technique utilized questionnaire and documentation. The questionnaire method is applied to collect data of independent and the dependent variable. The try out of research instrument were using validity and reliability test. Data analysis technique used is the technique of Binary Logistic Regression Analysis. The results of this study were: 1) The economic status of the family, the type of school and school status simultaneously have a significant influence on student interest in continuing study to higher education; 2) Family economic status partially has a significant impact on student interest in continuing to study on higher education; 3) Type of school partially has a significant impact on students' interest in continuing their studies to higher education; 4) Status of school does not affect the students' interest in continuing their studies to higher education; and 5) The more dominant variables to affect the interest of students in higher education to continue their studies is variable economic status. Keywords: Family Economic Status, Type of School, School Status, Student Interest in Continuing Studies